Bioactive tri/dicalcium silicate cements for treatment of pulpal and periapical tissues. (15th September 2019) - Primus, Carolyn M.; Tay, Franklin R.; Niu, Li-na
Graphical abstract: Abstract: Over 2500 articles and 200 reviews have been published on the bioactive tri/dicalcium silicate dental materials. The indications have expanded since their introduction in the 1990s from endodontic restorative and pulpal treatments to endodontic sealing and obturation. Bioactive ceramics, based on tri/dicalcium silicate cements, are now an indispensable part of the contemporary dental armamentarium for specialists including endodontists, pediatric dentists, oral surgeons andfor general dentists. This review emphasizes research on how these materials have conformed to international standards for dental materials ranging from biocompatibility (ISO 7405) to conformance as root canal sealers (ISO 6876). Potential future developments of alternative hydraulic materials were included. This review provides accurate materials science information on these important materials. Statement of Significance: The broadening indications and the proliferation of tri/dicalcium silicate-based products make this relatively new dental material important for all dentists and biomaterials scientists. Presenting the variations in compositions, properties, indications and clinical performance enable clinicians to choose the material most suitable for their cases. Researchers may expand their bioactive investigations to further validate and improve materials and outcomes.